Multiplicity and rapidity dependence of strange hadron production in pp, pPb, and PbPb collisions at the LHC - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Ero, J.; Flechl, M.; Friedl, M.; et al. (My University, 2017)
Measurements of strange hadron (K-S(0), Lambda +(Lambda) over bar, and Xi(-)+(Xi) over bar (+)) transverse momentum spectra in pp, pPb, and PbPb collisions are presented over a wide range of rapidity and event charged-particle multiplicity. The data were collected with the CMS detector at the CERN LHC in pp collisions at root s= 7 TeV, pPb collisions at root(NN)-N-s= 5.02 TeV, and PbPb collisions at root(NN)-N-s = 2.76 TeV. The average transverse kinetic energy is found to increase with multiplicity, at a faster rate for heavier strange particle species in all systems. At similar multiplicities, the difference in average transverse kinetic energy between different particle species is observed to be larger for pp and pPb events than for PbPb events. In pPb collisions, the average transverse kinetic energy is found to be slightly larger in the Pb-going direction than in the p-going direction for events with large multiplicity. The spectra are compared to models motivated by hydrodynamics. (c) 2017 The Author(s). Published by Elsevier B.V.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Collaboration, C. M. S. (2017). Multiplicity and rapidity dependence of strange hadron production in pp, pPb, and PbPb collisions at the LHC. Physics Letters B, 768, 103-129. doi:10.1016/j.physletb.2017.01.075
Keywords: Cms; Physics; Heavy Ion; Spectra; Radial Flow; Quark-Gluon Plasma